2018
DOI: 10.3415/vcot-17-03-0042
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Radiological Measures of Fracture Healing

Abstract: The formulation of appropriate postoperative strategies, following fracture repair, currently involves an understanding of radiological and clinical outcome measures. This study has evaluated several modalities used to assess the progression of bone healing in a sheep tibial segmental defect model. Measures of defect optical density and volumetric data including bone density (BD), bone volume (BV) and bone mass (BM) were compared with qualitative data involving visual appraisal of radiographs [% bridging callu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
12
0
2
Order By: Relevance
“…Implant failure, infection and severe fractures requiring subject exclusion have been reported in bone tissue engineering studies involving external fixation or internal fixation with intramedullary pins in sheep 2 , 27 , 28 . Field and Ruthenbeck 23 reported no complications following interlocking nail fixation in sheep. However, animals in their study were supported by a sling in the first three weeks after surgery.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Implant failure, infection and severe fractures requiring subject exclusion have been reported in bone tissue engineering studies involving external fixation or internal fixation with intramedullary pins in sheep 2 , 27 , 28 . Field and Ruthenbeck 23 reported no complications following interlocking nail fixation in sheep. However, animals in their study were supported by a sling in the first three weeks after surgery.…”
Section: Discussionmentioning
confidence: 94%
“…It must also replicate clinical conditions and be consistent with gait and biomechanical characteristics of the target species. Lastly, it should be amenable to imaging-based assessment while not compromising the well-being 21 23 . In this study, the dorsomedial approach was selected to expose the middle third of the tibial shaft.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on bone formation and fracture healing that evaluated PV and the PVR found that bone formation was correlated with PV on digital radiographs. 12,13,17,18 Although this study was performed as a multi-hospital case study, PVR was used as a measure of bone mineral areal density because measured data had been normalized to the values recorded on the humeral condyle at each time point. Since IIO involves decreased bone mineral density in the cortical bone beneath the plate, we defined IIO as a decrease in the PVR.…”
Section: Discussionmentioning
confidence: 99%
“…Although dual energy X-ray absorptiometry and quantitative computed tomography are the most popular methods for measuring bone mineral density, the pixel value of digital radiographs is correlated with bone mineral density in human medicine. 11,12 Radiographic regions of interest have been useful in assessing the healing process of tibial fractures in sheep 13 ; however, the use of radiographic bone density (grey levels) in evaluating the healing process of radial fractures in toy breeds have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…For the diagnosis of bone healing in fracture patients, most clinicians usually rely on clinical and imaging examinations, but the evaluation criteria vary greatly [3]. Therefore, Peter JO and Field JR started to use quantitative indicators to judge bone healing from the perspective of mechanics and imaging, respectively [4,5]. The fracture healing process is a continuous process over time [6].…”
Section: Introductionmentioning
confidence: 99%